Understanding India's Services Revolution - Gupta, Poonam; Gordon, James (Washington, D.C. : International Monetary Fund, 2004)
This paper analyzes the factors behind the recent growth of India's services sector. The high growth of services output in the 1990s was mostly due to the rapid expansion of communication, banking, business services (including the IT sector) and community services. While factors such as a high income elasticity of demand for services, increasing input usage of services by other sectors, and rising exports, were important in boosting services growth in the 1990s, supply side factors including reforms and technological advances also played significant roles. Going forward, the growth potential of Indian services exports is well known, but the paper also finds considerable scope for growth in the Indian service economy provided that deregulation continues. In addition, the paper shows that employment growth in the Indian services sector has been quite modest, thus underscoring the need for industry and agriculture to also grow rapidly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet